Long-term motor stimulant effects of (+)-4-propyl-9-hydroxynaphthoxazine (PHNO), a dopamine D-2 receptor agonist: interactions with a dopamine D-1 receptor antagonist and agonist. - Martin-Iverson, M; Iversen, S; Stahl, S (1988)
Rats were given continuous infusions of (+)-4-propyl-9-hydroxynaphthoxazine (PHNO, 5 micrograms/h), a dopamine D-2 receptor agonist, using subcutaneous implants of ALZET osmotic minipumps. It was observed that tolerance occurred to the motor stimulant effects of PHNO during the light cycle of each day, but not during the dark cycle. Rather, the motor stimulant actions of PHNO were gradually augmented during successive nights. Daytime tolerance to the stimulant actions of PHNO was reversed by a mild environmental stress or by administration of the D-1 receptor agonist, SKF 38393 (6 mg/kg i.p.). Co-administration of the dopamine D-1 receptor antagonist, (SCH 23390, 20 micrograms/h s.c. by ALZET osmotic minipumps), initially blocked the motor stimulant actions of PHNO and also attenuated the reversal of tolerance to PHNO produced by stress, without blocking the actions of stress on activity in vehicle-infused animals. These results indicate that tolerance to the behavioural effects of PHNO may result from a loss of activation of D-1 receptors by endogenous DA.